A review of the concept of resilience in the field of disasters and its evolution - Carrio Carro, Luis; Castro Delgado, Rafael; Arcos González, Pedro (Revista Española de Comunicación en Salud, 2019)
Introduction: The resilience, as the ability to overcome adverse events and be able to have a successful development despite very adverse circumstances (disasters, wars, emergencies, severe trauma, etc.), has taken a great interest in recent years and has emerged as a key concept in disaster risk management. The purpose of this article is to present an integrated perspective on resilience through an extensive review of its literature over time. Method: Major health electronic databases were searched to retrieve critical relevant publications about the conceptual framework of resilience. Results: A total of 37 publications were included in the final analysis of this document. Definitions have evolved over time, but essentially the term ‘resilience’ is understood as referring to positive adaptation -the ability to maintain or recover mental health-, despite experiencing adversity. The interaction between personal, biological and environmental sources of resilience is also considered. Conclusion: The number of papers published by the term ‘resilience’ in their titles has been growing steadily over recent years. Resilience is a new term that requires greater conceptual clarification, mainly because of its importance as an example of human potential in facing disasters.